UNEMPLOYMENT AS A SOCIAL INDICATOR OF ECONOMIC SECURITY - Abdurahimov Abdurasul Abdunosirovich; Narzullaev Nozimjon Sobirjanovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information on unemployment, the unemployment index, and the global unemployment rate